Erratum to: Search for squarks and gluinos in final states with one isolated lepton, jets, and missing transverse momentum at √s=13 TeV with the ATLAS detector - Aad, Georges; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Schöning, André; et al. (The European physical journal. C, Particles and fields, 2021)
A correction to this paper has been published: 10.1140/epjc/s10052-021-09344-w
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
ATLAS Collaboration: G. Aad, F. Bartels, M.M. Czyrylo, S. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, A. Schoening, H.-C. Schultz-Coulon, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue [und viele weitere]
Gesehen am 17.12.2021